Computational Analysis of Average Waiting and Arrival Times - Ahad, Nor Aishah; Okwonu, Friday Zinzendoff; Zulkifli, Malina; Md Yusof, Zahayu; Ogini, Nicholas Oluwole (Hunan University Natural Sciences, 2022)
Over the years, the drift from public to private schools has overwhelmed parents' and guardians' imagination due to teachers' and pupils' waiting times and the influence of parents in private and public schools. The government has also slowed parental emotions to send their children to public schools due to the lack of basic teaching tools, well-trained teachers, and vital infrastructure in many states in Nigeria. As a result, private individuals with inadequate educational management backgrounds started establishing schools as a business concern without proper regulations on teachers' recruitment, vital and basic school facilities. The proliferation of substandard private and public schools has led to waiting time problems. This article describes novel computational procedures to compute the average waiting and arrival time. The procedures investigate teachers and pupils' average arrival and waiting times for public and private primary schools in each class in a local government area in Delta State, Nigeria. A simple random sampling procedure was applied. The study intends to determine whether the mean waiting or arrival time of teachers and pupils for each class for the period under review is equal. The data set was subjected to further mean analysis and analysis of variance. The F statistic was obtained and compared with the F critical value, which resulted in the rejection of the null hypothesis at a 5% level of significance. The analysis indicated that the average waiting time for teachers' arrival in each class is not equal and the average waiting time for pupils' arrival is not equal, hence the null hypothesis's rejection. The study revealed that the average waiting time for public and private school pupils in the schools investigated is 17 minutes. In comparison, the average waiting time of teachers for both public and private schools is approximately 6 minutes. This study affirmed that waiting time problems exist in public and private schools